Importance of Personality in Gifted Children's Identity Formation - Zuo, Li. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This paper discusses the outcomes of a study that examined the importance of personality to identity formation in Terman's sample of 1,528 intellectually gifted children in 1936 and 1940. Based on the children's responses to questions concerning their occupational choice and factors that influenced their decision, participants were classified into one of the following four identity statuses; (1) Identity Achievement; (2) Moratorium, which indicated a participant had a definite occupational goal in mind but the current occupation was not yet the choice for life work; (3) Foreclosure, which indicated the person had a definite goal and a choice for life work, but the commitment was made because of family or ethnic background, family influences, or because previous dreams were made impossible by circumstances; and (4) Diffusion, which indicated the person had no goals nor commitment to any occupation as life work. Comparisons among the four identity statuses and between the two subgroups that followed progressive and regressive pathways in their identity development demonstrated the differences in personality characteristics. Positive traits such as perseverance, purposfulness, desire to excel, and self-confidence were found conducive to the successful identity formation and to the adoption of the progressive pathway in identity development. (Contains 43 references and five tables.) (CR)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New Orleans, LA, April 24-28, 2000).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adults; Biological Influences; Career Choice; Children; Gifted; Identification (Psychology); Life Satisfaction; Performance Factors; Personality Traits; Self Concept; Self Esteem; Reports, Research; Speeches/Meeting Papers